Improving mathematical communication skills with the Realistic Mathematics Education approach - Fajar Solidman Larosa; Nina Ardianti Dewi; Sudirman Sudirman; Nurhabiba Meha; Hasratuddin Hasratuddin; Dian Armanto (Inovasi Kurikulum, 2026)
Mathematics learning is important to develop from elementary school because at this stage students are developing their thinking and learning processes. This study aims to improve fifth-grade students' mathematical communication skills through the Realistic Mathematics Education (RME) approach. The method used is exploratory sequential mixed methods, starting with the collection and analysis of quantitative data, followed by the qualitative stage to deepen the findings. The study was conducted at SD Negeri 1 Syamtalira Bayu, North Aceh, with a sample of 21 fifth-grade students. Quantitative analysis used the N-Gain test, while qualitative analysis was carried out through data reduction, data presentation, and drawing conclusions for students with low, medium, and high communication ability categories. The quantitative results showed an N-Gain value of 0.65, which is in the medium category. This indicates that fraction learning with the RME approach is effective in improving students' mathematical communication skills. The results of the qualitative data analysis showed that students with high and medium levels of mathematical communication skills increased their achievement on mathematical communication ability indicators after the treatment. Meanwhile, students with low communication skills did not show an increase in achievement on indicators of mathematical communication ability.   Abstrak Pembelajaran Matematika penting dikembangkan sejak sekolah dasar karena pada fase ini murid sedang membangun proses berpikir dan belajar. Penelitian ini bertujuan meningkatkan kemampuan komunikasi matematis murid kelas V melalui pendekatan Realistic Mathematics Education (RME). Metode yang digunakan adalah exploratory sequential mixed methods, dimulai dari pengumpulan dan analisis data kuantitatif, kemudian dilanjutkan dengan tahap kualitatif untuk memperdalam temuan. Penelitian dilaksanakan di SD Negeri 1 Syamtalira Bayu, Aceh Utara, dengan sampel 21 murid kelas V. Analisis kuantitatif menggunakan uji N-Gain, sedangkan analisis kualitatif dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan pada murid dengan kategori kemampuan komunikasi rendah, sedang, dan tinggi. Hasil kuantitatif menunjukkan nilai N-Gain 0,65, berada pada kategori sedang. Hal ini menunjukkan bahwa pembelajaran pecahan dengan pendekatan RME efektif untuk meningkatkan kemampuan komunikasi matematis murid. Hasil analisis data kualitatif menunjukkan murid dengan kemampuan komunikasi matematis tinggi dan sedang mengalami peningkatan ketercapaian indikator kemampuan komunikasi matematis setelah adanya perlakuan. Sementara itu, murid dengan kemampuan komunikasi rendah tidak mengalami peningkatan ketercapaian indikator kemampuan komunikasi matematis. Kata Kunci: kemampuan komunikasi matematis; Realistic Mathematics Education; RME; sekolah dasar